2022
DOI: 10.1111/jfb.15007
|View full text |Cite
|
Sign up to set email alerts
|

Diel migration pattern of pink salmon fry in small streams

Abstract: Downstream migration is a critical stage in the anadromous salmonid life cycle, but previous studies have shown different results between rivers or surveys for the diel downstream migration pattern of the fry of the pink salmon Oncorhynchus gorbuscha. We investigated the diel migration pattern of pink salmon fry in three small streams. Our results showed that pink salmon fry migrate mainly within a few hours after sunset; 89.9% of migration occurred between 18:00 and 23:00. Therefore, the results indicated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…In addition, dippers sometimes prey on salmon fry (Obermeyer et al, 2006; Ormerod, 1985; Ormerod & Tyler, 1986, 1991). Since most salmon fry mainly emerge during spring and summer (Kirillov et al, 2018; Pavlov et al, 2008; Yamada et al, 2022), salmon fry may be used as a food resource by dippers during this period. Therefore, spawning by anadromous salmonids may compensate for declines in the abundance of aquatic invertebrates during various seasons.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, dippers sometimes prey on salmon fry (Obermeyer et al, 2006; Ormerod, 1985; Ormerod & Tyler, 1986, 1991). Since most salmon fry mainly emerge during spring and summer (Kirillov et al, 2018; Pavlov et al, 2008; Yamada et al, 2022), salmon fry may be used as a food resource by dippers during this period. Therefore, spawning by anadromous salmonids may compensate for declines in the abundance of aquatic invertebrates during various seasons.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, dippers sometimes prey on salmon fry (Obermeyer et al, 2006; Ormerod, 1985; Ormerod & Tyler, 1986, 1991). Since most salmon fry mainly emerge during spring and summer (Kirillov et al, 2018; Pavlov et al, 2008; Yamada et al, 2022), salmon fry may be used as a food resource by dippers during this period. Therefore, spawning by anadromous salmonids may compensate for declines in the abundance of aquatic invertebrates during various seasons.…”
Section: Discussionmentioning
confidence: 99%
“…We used stakes to fix the nets to the streambed so that the net openings spanned from the stream surface to the streambed. All surveys started between 18:00 and 18:30 and finished between 22:15 and 22:45 because downstream migration of pink salmon fry is almost always observed at night (Kirillov et al, 2018;Neave, 1955), and its peak was found at approximately 20:00 in this study area (Yamada, Urabe, et al, 2022). However, if pink salmon fry were not collected throughout the first to fourth trials, the survey was finished between 21:15 and 21:45.…”
Section: -3 Estimation Of the Total Number Of Fry Migrantsmentioning
confidence: 99%
“…We placed one or two drift nets (Matsui Corp., Tokyo, Japan; 50 cm squared opening, 100 cm long, 3 mm mesh), which are often used to capture salmon fry (Hintz & Lonzarich, 2012;T. A. Johnston, 1997;Yamada, Urabe, et al, 2022), at a sampling point for 15 minutes at hourly intervals (Yamada, Urabe, et al, 2022). Since long-term sampling with drift nets would result in higher fry mortality, we set the sampling duration to be as short as possible.…”
Section: -3 Estimation Of the Total Number Of Fry Migrantsmentioning
confidence: 99%
See 1 more Smart Citation